The Urgency of Life-Long Learning for Students in Biology Learning - Intan Rizky Amalia; Muhammad Syaipul Hayat (Universitas Wiralodra, 2021)
Education is a need for every child to have insight and hope for goals because basics education is helpful until the end of life. The existence of life-long learning indicators is very relevant to be applied by students in learning biology. These indicators include complex thinking, information processing, effective communication, collaboration/cooperation, and thinking habits. This study aims to determine the urgency of providing life-long learning for students in biology learning. The research method uses qualitative methods, the research instrument used in this study is a questionnaire. The results showed that the student's response was in the high category with a percentage of 60%, which means that students already understand the concept of life-long learning but have not applied it in their daily lives. 60.9% of students responded that life-long learning had not been implemented in biology learning at school and agreed if it was applied in biology learning. Therefore, the provision of life-long learning for students in biology learning is considered very important to apply.